VD_FINDINFO Arrêt / 2018 / 251 vom 23. Mai 2018 - VD Tribunal cantonal (2018)
LOI FÉDÉRALE SUR L'ASSURANCE-INVALIDITÉ, CONTRIBUTION D'ASSISTANCE, REJET DE LA DEMANDE | 42quater LAI, 42quinquies LAI, 42sexies LAI, 39c RAI, 39f RAI, 39g RAI